Weed Management Options for Successful Dry Direct Seeded Rice in Conservation Agriculture - Sarkar, Ayan; Mandal, Abhijit; Singh, Teekam (Chronicle of Bioresource Management, 2021)
Conservation agriculture emerged as a potential resource conservation technology against conventional puddled transplanting rice. In DDSR, the absence of standing water and conventional tillage, seedling size differentiation gives weed a prolific advantage over rice plants. Sometimes weeds could cause loss up to 100%. Preventive approaches like pure seeds, weed free bunds and irrigation channels, seed quarantine aimed to minimize weed seed entry in to a field. Hand weeding, stale seed bed and non-selective herbicides like paraquat or diquat are the most important components in IWM of DDSR in CA based system. Some cultural practices like high seed rate, early sowing, mulching, brown manuring and cover crops are found beneficial against weeds. The varieties like- ‘PR 120’, ‘PR 108’, ‘PI 312777’ having vigorous early growth, vertical leaf orientation and more tillering potential are found suitable in Indian condition for DDSR.